Women-led police stations: reimagining the policing of gender violence in the twenty-first century. (28th May 2022) - Carrington, Kerry; Sozzo, Máximo; Ryan, Vanessa; Rodgers, Jess
ABSTRACT: When domestic violence was criminalised in countries like Australia, United States and United Kingdom, many saw this as a victory, as the state taking responsibility for violence against women. The problem was that its policing was delegated to a masculinised police force ill-equipped to respond to survivors of gender violence. Latin America took a different pathway, establishing women-led police stations designed specifically to respond to the survivors of gender violence. Our research team looked for inspiration to reimagine the policing of gender violence in the twenty-first century from the victim-centred women-led police stations that emerged in Argentina in the 1980s. By emphasising a preventative over a punitive approach, multi-disciplinary teams of police, social workers, psychologists and lawyers offer survivors a gateway to support, instead of just funnelling them into the criminal justice system. Surveying gender violence sector workers and members of the general public, we sought views on the potential of adapting the protocols of these specialist police stations to Australia. We argue that if staffed by appropriately trained teams to work from both gender and culturally sensitive perspectives, women-led victim friendly police stations could side-step some of the unintended consequences of criminalisation, pathing the way for reimagining the policing of gender violence. Framed by southern criminology the project aims to redress the biases in the global hierarchy of knowledge, by reversing the notion that policy transfer can only flow from the countries of the Global North to the Global South.